Determination of Water Quality Parameters Using Microwave Nondestructive Method - Al-Mattarneh, Hashem; Dahim, Mohammed (International Journal of Engineering and Technology, 2018)
This paper presents an investigation of microwave reflection and dielectric properties measured by the open-ended rectangular waveguide in the frequency range of 8-12 GHz to determine water quality parameters. Microwave method shows a potential to determine the salinity and some water quality index. The complex permittivity called dielectric properties in the microwave frequency were calculated from the microwave reflection. Several water quality parameters such as salinity, turbidity and temperature were related to the measured microwave properties of water using mathematical regression models. The results indicate that the reflection and dielectric properties of water decrease with increasing the temperature of water samples. The salinity of water sample increase the loss factor and decrease the dielectric constant of the water sample. Also, the reflection of the microwave signal and dielectric properties decrease with increasing microwave frequency and turbidity of the water. The microwave system which used microwave reflection and dielectric properties of water bodies could make the determination of water quality parameters and water indexes more simple, fast, relatively low cost compared with the current used method. Microwave method for water quality may also save a good amount of time and money compared to existing standard methods. Further investigation is needed to determine the possibility of using microwave method for predicting other water quality factors.Â Â